3D Media in the Transversal Era: A Techno-Cultural Analysis. - Bauer, DB (Afterimage, 2024)
Transversal media move. They move with ease across a variety of interfaces, formats, materials, software, hardware, uses, and communities of practice. In this article, transversal media is an umbrella term used to classify media objects with the same underlying form that takes shape across a variety of materialities through freeze and flow states. Specific to 3D data, 3D transversal media are a distinct media type that have emerged from the development and proliferation of 3D media technologies, specifically the 3D printer, 3D scanner, and extended reality (XR) devices. The central characteristic of 3D transversal media is the ability to move back and forth across digital and atomic forms. Transversality offers an alternative to understanding and speaking of the digital and atomic as opposites, while also acknowledging the differences and similarities across those material transmutations. For instance, the same 3D transversal media object can be many things simultaneously: an animation on a screen, an object inside a virtual reality experience, a 3D-printed plastic figurine, a projected hologram, and more. This article tracks the complexities of 3D transversal media when they move across their individual and networked states, and moreover, the linked cultural and technological significance of that movement. This approach reveals how technology and media can inherit and reproduce hegemonic cultural ideologies and practices—whether intentional or not. To concretize this, the article concludes with a case study on Thutmose's well-known bust of Nefertiti, now a 3D transversal object, and how its transversal affordances converge and interact with global cultural politics—specifically in this case, those related to colonialism and imperialism.